2022
DOI: 10.1101/2022.10.25.513675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian Pharmacometrics Analysis of Baclofen for Alcohol Use Disorder

Abstract: Alcohol use disorder (AUD) also called alcohol dependence is a major public health problem, which affects almost 10% of the world's population. Baclofen as a selective GABA_B receptor agonist has emerged as a promising drug for the treatment of AUD, however, its optimal dosage varies according to individuals, and its exposure-response relationship has not been well established yet. In this study, we use a principled Bayesian workflow to estimate the parameters of a pharmacokinetic (PK) population model from Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The posterior distribution encompasses all possible parameter combinations that produce a simulation output that explains the data with quantifying the uncertainty in estimation, which is critical for model comparison, selection and averaging, hypothesis testing, and decision-making process. Bayesian inference also allows us to integrate the prior knowledge in inference and prediction (Gelman et al, 2014) e.g., the physiological, anatomical, or clinical knowledge to maximize the model predictive power against measurements (Hashemi et al, 2021; Baldy et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior distribution encompasses all possible parameter combinations that produce a simulation output that explains the data with quantifying the uncertainty in estimation, which is critical for model comparison, selection and averaging, hypothesis testing, and decision-making process. Bayesian inference also allows us to integrate the prior knowledge in inference and prediction (Gelman et al, 2014) e.g., the physiological, anatomical, or clinical knowledge to maximize the model predictive power against measurements (Hashemi et al, 2021; Baldy et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although, we have shown that this non-parametric approach is able to accurately estimate the spatial map of epileptogenicity across whole-brain areas, it required a reparameterization over model configuration space to facilitate efficient exploration of the posterior distribution in terms of computational time and convergence diagnostics (Jha et al, 2022). In the presence of metastability in the state space (see Fig 1, Fig S1), MCMC methods require either more computational cost or intricately designed sampling strategies (Gabrié et al, 2022; Jha et al, 2022; Baldy et al, 2023), whereas SBI allows for efficient Bayesian estimation with-out the access to the full knowledge on the state space representation of a system (Baldy et al, 2024). Note that we used the data features derived from only firing rates, while the information related to membrane potential activities was treated as missing data (i.e., no access to the full state space behavior).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the objective function plays a crucial role in determining the estimation through optimization methods (Svensson et al, 2012; Hashemi et al, 2018). The error explanation with distance metrics such as RMSE is limited in accurately capturing the underlying data generation process (Baldy et al, 2023). This is because when generative parameters remain unchanged but when dynamic noise is introduced, the time-series can show large fluctuations, resulting in deviations from the observed data.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the NUTS calibrates the number of steps and step-size of the leapfrog integrator (in solving the Hamiltonian equations of motion) during a warm-up phase to achieve a target Metropolis acceptance rate. For more details see Betancourt (2013); Baldy et al (2023). Moreover, Stan offers alternative methods such as MAP estimation using L-BFGS optimization, automatic differentiation for efficient gradient computation, and various diagnostics to assess the convergence of the inference process (see https://mc-stan.org).…”
Section: Methodsmentioning
confidence: 99%